Event-Triggered Adaptive Control for Tank Gun Control Systems - JianPing Cai; Rui Yu; Qiuzhen Yan; Congli Mei; Binrui Wang; Lujuan Shen (IEEE Access, 2019)
In this paper, an event-triggered adaptive control scheme is proposed for the gun control system of a tank subject to not only external disturbances but also uncertain modeling errors and unknown parameters. Compared with the existing results, the upper bound function of modeling errors is unknown. Therefore, the traditional event-triggered control method cannot be applied directly to handle the effect caused by the modeling errors. To solve this problem, a smooth function $sg(·)$ is introduced to estimate the bound of modeling errors, such that their effects on system stability are successfully compensated. The simulation results are provided to illustrate the effectiveness of the proposed control scheme.